2018
DOI: 10.1364/ol.43.002414
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-modulated directional torsion sensor based on in-line optical fiber Mach–Zehnder interferometer

Abstract: In this Letter, we demonstrated an intensity-modulated directional torsion sensor based on an in-line Mach-Zehnder interferometer in single-mode fiber. A non-circular symmetric perturbation is created to excite non-circular symmetric cladding mode and then interference with the core mode at the second perturbation. An initial rotation angle is designed between two perturbations for the purpose of discriminating the torsion direction. Both experimental and theoretical results enforce that the spectral peak/dip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Chalyan T et al proposed a photonic biosensor based on Si 3 N 4 Asymmetric Mach-Zehnder interferometer (MZI), which can detect aflatoxin, and its best volumetric sensitivity is 104 rad/RIU (Chalyan et al 2016). Fu et al demonstrated an intensity-modulated directional torsion sensor based on an in-line MZI in single-mode fiber (Fu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Chalyan T et al proposed a photonic biosensor based on Si 3 N 4 Asymmetric Mach-Zehnder interferometer (MZI), which can detect aflatoxin, and its best volumetric sensitivity is 104 rad/RIU (Chalyan et al 2016). Fu et al demonstrated an intensity-modulated directional torsion sensor based on an in-line MZI in single-mode fiber (Fu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the application of optical fiber sensors (OFSs) in twist sensing has intensified, due to their advantages of flexibility, light weight, and resistance to electromagnetic interference. Though many different schemes have been proposed, optical fiber twist sensors (OFTSs) can be mainly classified into two types: one interrogated with wavelength (e.g., specially designed fiber gratings [1][2][3][4][5][6][7][8], Sagnac interferometer [9][10][11], helical fiber structure [12][13][14]), and the other with intensity (e.g., Solc filter [15], Lyot filter [16], Mach-Zehnder interferometers [17][18][19]), and fiber gratings [20][21][22][23][24][25][26][27][28][29][30]. Note that for the first type, the wavelength measurement involves the use of expensive and bulky optical spectrum analyzer (OSA) or tunable narrow-linewidth laser, whereas for the second type, intensity measurement only requires an optical power meter (or photodetector), which allows more compact and cost-effective interrogation than the first type.…”
Section: Introductionmentioning
confidence: 99%
“…Optical fiber sensing technology has attracted extensive attention and great research enthusiasm in the field of metal ion monitoring due to its unique advances such as low cost, light weight, ease of use, small in size, multiplexing, remote sensing, and high sensitivity [4][5][6][7]. Up to now, optical fiber heavy metal ion sensors have been reported by utilizing fluorescence [8], surface-enhanced Raman scattering [9], surface plasmon resonance [10][11][12], and localized surface plasmon resonance (LSPR) [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%